2005
DOI: 10.1007/s00484-005-0003-x
|View full text |Cite
|
Sign up to set email alerts
|

France’s heat health watch warning system

Abstract: In 2003, a Heat Health Watch Warning System was developed in France to anticipate heat waves that may result in a large excess of mortality. The system was developed on the basis of a retrospective analysis of mortality and meteorological data in fourteen pilot cities. Several meteorological indicators were tested in relation to levels of excess mortality. Computations of sensibility and specificity were used to choose the meteorological indicators and the cut-offs. An indicator that mixes minimum and maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(122 citation statements)
references
References 23 publications
2
109
0
8
Order By: Relevance
“…In the European context, research in this area may be particularly important in transition countries (such as Slovakia), which have still not reached the level of actions as in some of the most developed countries, where successful efforts to minimize the negative effects of heat (and weather in general) on their populations have already been made (e.g. Pascal et al, 2006;Fouillet et al, 2008;Lowe et al, 2011;Bittner et al, 2013). These results could therefore be particularly useful for future public health interventions, the implementation of which is below an adequate level in Slovakia.…”
Section: Discussionmentioning
confidence: 99%
“…In the European context, research in this area may be particularly important in transition countries (such as Slovakia), which have still not reached the level of actions as in some of the most developed countries, where successful efforts to minimize the negative effects of heat (and weather in general) on their populations have already been made (e.g. Pascal et al, 2006;Fouillet et al, 2008;Lowe et al, 2011;Bittner et al, 2013). These results could therefore be particularly useful for future public health interventions, the implementation of which is below an adequate level in Slovakia.…”
Section: Discussionmentioning
confidence: 99%
“…Persistence of hot days was investigated as many studies highlighted how this factor represents an additional risk. It is important to note that heat waves are often defined according to their length (Colacino and Conte, 1995;Huynen et al, 2001;Robinson, 2001;Pascal et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…111 They include forecasting, predicting possible health outcomes, triggering effective and timely response plans, targeting vulnerable populations, and communicating prevention responses. Public health authorities need to upgrade existing emergency programmes and conduct exercises to enhance preparedness for anticipated health risks due to new extreme events such as sea level rise, saline water intrusion into drinking water courses, and severe flooding from storm surges.…”
Section: Early Warning Systems For Extreme Eventsmentioning
confidence: 99%
“…The 2003 European heatwave, which killed up to 70 000 people led France to introduce a heatwave warning system and a national action plan. 111 Health worker training was modified, urban planning altered, and new public health infrastructure developed. The 2006 heatwave suggested that these measures had been effective, with 4400 fewer anticipated deaths.…”
Section: Actions To Reduce Burdens Of Heatwavesmentioning
confidence: 99%
See 1 more Smart Citation